(untitled) (Jurnal AbdiMas Nusa Mandiri, 2026)
Pregnancy is a crucial period that requires ongoing health monitoring. The Indonesian government, through the Ministry of Health, has developed the SATU SEHAT app as an integrated digital platform to support health services, including maternal and child health. However, uptake of this app at the community level remains low due to limited digital literacy. This community service activity aims to enhance the knowledge and skills of pregnant women in using the SATU SEHAT app as a tool for monitoring pregnancy health. The methods employed include outreach, education, and direct support for pregnant women in Banjar Kemuning, Sidoarjo Regency. The results of the activity and evaluation indicate an improvement in participants’ understanding across all indicators (knowledge, attitudes and skills) regarding the importance of maternal health, with an increase of 45.10%. There was also a 48.35% improvement in the use of basic features of the SATU SEHAT app. It is hoped that this activity will support improvements in the health status of pregnant women and the optimisation of digital health service utilisation.